The Use of Social Media in Raising Awareness of Nature Conservation - ADENIRAN, Adeyinka Adepoju; BABATUNDE , Olayinka Funmi (Westscience Press, 2026)
The rapid growth of social media has transformed the way environmental information is communicated and accessed by the public. This study aims to examine the role of social media in raising awareness of nature conservation. A quantitative research approach was employed using a survey method involving 155 active social media users. Data were collected through a structured questionnaire measured on a five-point Likert scale. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25, including descriptive statistics, validity and reliability tests, correlation analysis, and simple linear regression. The results show that social media use has a positive and significant effect on nature conservation awareness. The correlation analysis reveals a strong relationship between social media use and conservation awareness, while regression analysis indicates that social media explains 37.5% of the variance in awareness levels. These findings suggest that social media serves as an effective platform for disseminating conservation-related information and enhancing public understanding and concern for environmental protection. The study provides practical implications for environmental organizations and policymakers to optimize social media strategies in promoting nature conservation awareness.